On the issue of automating the workflow design based on algebra-algorithmic and ontological tools - Ovdii, O.M. (Інститут програмних систем НАН України, 2019)
The article presents the concept of a system for automated workflow design based on algebra-algorithmic and ontological tools. The previously developed applied ontology for program design has been expanded with new concepts related to the workflow design. The existing approaches are analysed and architecture for system that under development is proposed. The work of the system is illustrated by the example of the development of the Apache Oozie workflow for analyzing large amounts of data on the distributed Apache Hadoop platform. It is shown that the combination of ontology and algebra-algorithmic tools provides significant potential for adaptation, optimization, integration and modification. In addition, the high level of abstraction provided by these tools facilitates the understanding of the designed workflows by both people and software agents, simplifying teamwork, workflow sharing and reuse. The results of a quantitative assessment of the proposed tools indicate that they can contribute to a significant increase in development productivity and reduce labor costs.Problems in programming 2019; 1: 37-47